Housing Associations and Relationship Marketing: Customers, Communication and Relationships - Hayat, Nasir (2006)
This dissertation focuses on relationships within the Housing Association market sector. It tries to answer the questions who are the real customers in this market and do key stakeholders in the business take priority over these customers. Also what sort of communication and relationship management do Housing Associations carry out and are there any issues that need to be taken into account in this area. The dissertation uses research carried out on a number of Housing Associations to draw its conclusions.